Политика и СМИ. Манитуляция сознанием - Михайлова, Л. О.; Минская, А. Г. (ХНУРЭ, 2012)
The media are one of the most important institutions of modern society. They perform multiple functions: inform, educate, promote, entertain. It is obvious that they play an important role in the formation, functioning and evolution of social consciousness as a whole. Moreover, the perception and interpretation of important events and developments in the country and the world in general, are carried out through and through the media.